An Innovative AI Blockchain Framework for Islamic Microfinancing - Katterbauer, Klemens; Hassan Syed; Laurent Cleenewerck de Kiev (Journal of Islamic Finance, 2022)
The digital economy has undergone significant transformations with blockchain becoming a household name in the fintech environment. Besides powering cryptocurrencies, blockchain technology enables power transactions in a variety of forms and enables decentralization which may reduce transaction costs. Islamic microfinance has become important with many new institutions arising in order to satisfy the demand for microfinance services while ensuring that these services comply with the Shariah Law. Cost of transactions and low degree of digitalization are the major obstacles with current solutions. We present an innovative blockchain artificial intelligence framework for the optimization of Islamic microfinance service provisioning as well as providing financial and transaction services in order to ease transactions and make them more secure and readily available. The framework was evaluated on a large dataset from the Central African Republic, and we could demonstrate strong performance of the AI-blockchain framework. The framework provides a viable solution for Islamic microfinancing to enhance transactions services and overcome some of the existing challenges with Islamic finance.